Community structure of phytoplankton at Nipah River, Jongkat District, Mempawah Regency - Kurniadi, Bambang; Rahayu, Sri; Putri, Qori Yustika; Agamawan, Lalu Panji Imam (AGRICOLA, 2025)
Nipah River activities can affect water quality. Phytoplankton is a biological indicator for assessing water quality and aquatic tropihic levels. The purpose of this study is to analyze the community structure of phytoplankton in the Nipah River, Jongkat district, Mempawah Regency. The study was conducted from August to October 2022. Phytoplankton which found were composed by 4 classes, they are Bacillariophyceae, Zygnematophyceae, Cyanophyceae, and Chlorophyceae. Index of diversity (H’) ranged from 1.92-2.18, index of evenness (E) ranged from 0.9-1.0, and index of dominance ranged from 0.12-0.16. The diversity of phytoplankton in the Nipah River is categorized as moderate, the distribution of individuals between genera at each station is evenly, and there is no dominant species.